Malnutrition in HIV infected children on antiretroviral drugs in a cohort of Ghanaian children. Issue 12 (December 2021) - Intiful, Freda D.; Abdulai, Hikmatu; Nyarko, Ruth; Tette, Edem; Asante, Matilda
Abstract: Background: HIV infected children are at increased risk of malnutrition which worsens the depressed immune system, leading to poor disease prognosis. Aim: To assess the nutritional status of children between 6-12 years on antiretroviral drugs (ARV) at two health facilities in Accra. Methods: The study design was cross sectional among children between 6 and 12 years being administered with antiretroviral drugs at two hospitals in Accra. A purposive sample of 100 children was used. Height and weight measurements were taken and used to compute z-scores for stunting, underweight and wasting. Haemoglobin status was obtained from their folders. A semi-structured questionnaire was used to obtain sociodemographic data and a 24-hour dietary intake used to assess nutrient intakes. Data was analyzed using IBM SPSS version 20.0. Nutrient analysis was done using Micro diet version 3.0. Data was summarized using means and percentages. Chi-squared test was used to test for associations and statistical significance set at p < 0.05. Results: The prevalence of stunting, underweight and wasting was reported as 28%, 16% and 13% respectively. Girls were more stunted and wasted compared to boys. Mean haemoglobin concentration was 10.12 ± 2.77 g/dl. Mild, moderate and severe anaemia were reported in 14.2%, 41.1% and 12.5% of the children respectively. Apart from carbohydrates, less than 50% of the children were able to meet their requirements for the other nutrients". Conclusions: Our findings reveal high level of malnutrition among the children receiving ARV. There is the need for targeted nutrition interventions to improve the nutritional status of the children. Abstract : HIV; Malnutrition; Children; Ghana.